Red Seas : Ferdinand Smith and radical black sailors in the United States and Jamaica - Horne, Gerald (New York University Press, 2005)
During the heyday of the U.S. and international labor movements in the 1930's and 1940's, Ferdinand Smith, the Jamaican-born co-founder and second-in-command of the National Maritime Union (NMU), stands out as one of the most-if not the most-powerful black labor leaders in the United States. Smith's active membership in the Communist Party, however, coupled with his bold labor radicalism and shaky immigration status, brought him under continual surveillance by U.S. authorities, especially during the Red Scare in the 1950's. Smith was eventually deported to his homeland of Jamaica, where he.